Synthesis and Properties of Superparamagnetic Y-Fe2O3 - Kotsyubynsky, V.O.; Moklyak, V.V.; Hrubiak, A.B. (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
Method of nanodispersed g-Fe2O3 synthesis by thermal decomposition of iron citrate is proposed. The investigations of obtained oxides crystalline and magnetic structures are done. Nanodispersed g-Fe2O3 with sizes of coherent scattering regions about 4-7 nm was is only one phase after gel sintering at 200, 250 and 300оС; the particles of synthesized materials are in a state of magnetic ordering and in superparamagnetic state. The influence of magnetic dipole interparticles interaction on parameters of Mossbauer spectra is observed. The phenomenological model of the differences between nanodispersed g-Fe2O3 magnetic microstructures obtained after annealing at different temperatures is presented.